Ķīnas attiecības ar Baltkrieviju un Ķīnas attiecības ar Poliju 2006.-2016.g.: salīdzinājums - Skuza, Anna Dominika (Latvijas Universitāte, 2017)
This Master thesis shows the relations between Belarus and China in comparison to the relations between Poland and China. In the first chapter the author describes the political and economic situation in the three countries. The second chapter states about the political relations between Poland – the People’s Republic of China, Belarus and China, the New Silk Road and 16+1 formats. The third chapter covers the topic of the economic relations between the states. In the chapter no. 4 the author writes about the military cooperation issues. The last chapter shows the future plans and recommendations for the further cooperation.
The Relations of China with Belarus and China with Poland in 2006.-2016.: Comparison
Keywords: Valodniecība; Belarus; Poland; the People's Republic of China; economy; politics